Exercise‐induced elevations in cerebral blood velocity are greater in running compared to cycling at higher intensities. Issue 15 (12th August 2020) - Furlong, Rhodri J.; Weaver, Samuel R.; Sutherland, Rory; Burley, Claire V.; Imi, Gabriella M.; Lucas, Rebekah A. I.; Lucas, Samuel J. E.
Abstract: The optimal exercise intensity and modality for maximizing cerebral blood flow (CBF) and hence potential exposure to positive, hemodynamically derived cerebral adaptations is yet to be fully determined. This study compared CBF velocity responses between running and cycling across a range of exercise intensities. Twenty‐six participants (12 females; age: 26 ± 8 years) completed four exercise sessions; two mode‐specific maximal oxygen consumption (VO2max ) tests, followed by (order randomized) two incremental exercise protocols (3‐min stages at 35%, 50%, 65%, 80%, 95% VO2max ). Continuous measures of middle cerebral artery velocity (MCAv), oxygen consumption, end‐tidal CO2 (PET CO2 ), and heart rate were obtained. Modality‐specific MCAv changes were observed for the whole group (interaction effect: p  = .01). Exercise‐induced increases in MCAvmean during cycling followed an inverted‐U pattern, peaking at 65% VO2max (Δ12 ± 7 cm/s from rest), whereas MCAvmean during running increased linearly up to 95% VO2max (change from rest: Δ12 ± 13 vs. Δ7 ± 8 cm/s for running vs. cycling at 95% VO2max ; p  = .01). In contrast, both modalities had an inverted‐U pattern for PET CO2 changes, although peaked at different intensities (running: 50% VO2max, Δ6 ± 2 mmHg; cycling: 65% VO2max, Δ7 ± 2 mmHg; interaction effect: p  = .01). Further subgroup analysis revealed that the running‐specific linear MCAvmean response was fitness dependent (Fitness*modality*intensity interaction effect: p  = .04). Above 65% VO2max, fitter participants ( n  = 16; male > 45 mL/min/kg and female > 40 mL/min/kg) increased MCAvmean up to 95% VO2max, whereas in unfit participants ( n  = 7, male < mL/min/kg and female < 35 mL/min/kg) MCAvmean returned toward resting values. Findings demonstrate that modality‐ and fitness‐specific profiles for MCAvmean are seen at exercise intensities exceeding 65% VO2max . Abstract : This study compared cerebral blood flow (CBF) responses between running and cycling across a range of exercise intensities. Our findings demonstrate that exercise‐induced increases in CBF (as indexed from Doppler‐based measures of middle cerebral artery velocity, MCAv) during incremental running and cycling differ at higher exercise intensities, with the pattern of the MCAv response during running for fitter individuals dissociating from the regulatory influence of PCO2 at near maximal intensity (95% VO2max ). Thus, modality‐specific differences in beat‐to‐beat flow patterns may alter CBF regulation processes and affect the complex integration of factors regulating CBF during exercise.